Pengaruh Corporate Social Responsibility Terhadap Nilai Perusahaan dengan Prosentase Kepemilikan Manajemen Sebagai Variabel Moderating - Abriyani Puspaningsih; Isna Putri Rahmawati (Jurnal Aplikasi Bisnis, 2017)
This research was aimed to expose the effect of corporate social responsibility to the company's value with managerial ownership as a moderating variable. In this research, corporate social responsibility as dependent variable, company's value asindependent variable and •managerial. ownership as moderating variable.Sampels in this research were 41 manufacture company in Kompas Index 100 at 2008- 2009. Data processing in this research was supported by statistic program (SPSS). The data analyst' was carried on by regression analysisThe result from the analysis showed that corporate social responsibility was affected to company's value and managerial ownership was not a moderating variable in the relationship between corporate social responsibilityand company's value.